Influenza virus circulation in swine populations in various regions of the Republic of Kazakhstan (2018 - 2019) (Experimental biology, 2020)
In 2018 – 2019, 1104 nasopharyngeal swabs and 39 blood serums were collected from 2-6- month-old swine in peasant livestock farms located in seven regions of the Republic of Kazakhstan.Virological examination of 1104 samples in the polymerase chain reaction has resulted in the discovery of the genetic material of influenza A viruses in 26 biological samples (2.36% of the total number of examined swine). When subtyping RNA, influenza A/H1N1 virus was identified in 1.45% of samples, A/H3N2 in 0.54% of cases, А/H1sw2009 in 0,36% of samples.As a result of virological studies, three isolates from the North Kazakhstan oblast have been obtained from biological samples in chicken embryos that were identified as influenza A/H1N1 viruses in RT-PCR, HAI and NAI assays.Serological studies of 39 blood serums in the hemagglutination   inhibition assay have established that one sample (2.56% of the total number of examined serums) was positive for influenza A swine/Iova/15/30 (HSW1N1) virus, the antibody titer was 1:40. In three animal serums (7.69%), antibodies in the titers of 1:20-1:40 were detected against influenza A/California/ 04/09 virus (A/H1N1pdm). Nine serums (23.08%) were positive for A/Panama/2007/99(H3N2) virus with anti-hemagglutinin titers of 1:20-1:40.An enzyme immunoassay of 39 serums in six samples (15.38% of cases from the total number of examined samples) has revealed antibodies against A/H3N2 influenza virus.The results obtained during screening of biosamples in the polymerase chain reaction, hemagglutination inhibition assay, and enzyme immunoassay indicate the co-circulation of influenza viruses A/H1N, A/H3N2 and А/H1sw2009 in swine populations in Kazakhstan and the need for further monitoring studies of pathogens in order to timely detect the etiological agent of animal epizootic in livestock farms. Key words: virus, influenza, antigen, serum, antibodies, monitoring, circulation